Comparison of Health-Related Quality of Life, Psychological Symptoms, and Resilience in Patients With Hypothyroidism and Healthy Individuals - Amini, Zeinab; Hemmati Gorabi, Asal; Shirinpour, Saba (Mental Health and Lifestyle Journal, 2026)
The aim of the present study was to compare health-related quality of life, psychological symptoms, and resilience in patients with hypothyroidism and healthy individuals. This research employed a descriptive–analytical design within a causal-comparative framework. The statistical population consisted of patients with hypothyroidism who visited endocrine clinics in Rasht and their healthy companions in 2025. Using Cohen’s power analysis criteria, the sample size for each group was determined to be 90 participants (a total of 180 individuals), and purposive sampling was applied. The research instruments included the Health-Related Quality of Life Questionnaire (1992), the Connor–Davidson Resilience Scale (2003), and the Lovibond Psychological Symptoms Scale (1995). Data were analyzed using SPSS-26 through multivariate analysis of variance (MANOVA) and one-way ANOVA. The findings indicated a significant difference between patients and healthy individuals in health-related quality of life, resilience, and psychological symptoms (p < .05). Healthy individuals reported higher resilience, whereas patients with hypothyroidism reported lower health-related quality of life and higher psychological symptoms (p < .05). The results of the study suggest that hypothyroidism, in addition to its physical aspects, is associated with psychological and social challenges. Therefore, psychological and supportive interventions alongside pharmacological treatment may help enhance resilience and improve the quality of life in these patients.